Modelling and Performance Evaluation of an Air Handling Unit for an Air Treatment System with Regulated Outdoor-air Fraction. (May 2017) - Cui, X.; Mohan, B.; Islam, M.R.; Chua, K.J.
Abstract: An air treatment system has been proposed to reduce energy consumption and improve air quality. This system employs a lower outdoor-air fraction resulting in significant energy saving due to a reduced cooling load for the outdoor air intake. A computational model has been developed to determine the performance of the air handling cooling coil. The validation of the model showed good agreement with experimental data to within 5%. The supply air condition has been theoretically studied to demonstrate the influence of outdoor-air fraction and chilled water temperature. Simulation results indicate that a higher chilled water supply temperature can be adopted by reducing the outdoor-air fraction without compromising the supply air cooling capacity. Higher chilled water supply temperatures also lead to better coefficient of performance of the chiller. The energy consumption of the chiller could be reduced by up to 48% simply by reducing the outdoor-air fraction from 40% to 10%.